Microfluidic Visible‐Light Paternò–Büchi Reaction of Oxindole Enol Ethers. Issue 43 (8th September 2020) - Franceschi, Pietro; Mateos, Javier; Vega‐Peñaloza, Alberto; Dell'Amico, Luca
Abstract : A novel microfluidic visible‐light process for the functionalisation of oxindoles is reported. The chemistry is based on the reactivity of the corresponding enol ethers, which participate in a site‐, regio‐ and diastereoselective [2+2] heterocycloaddition (Paternò–Büchi) process. The mild reaction conditions, the use of available ketones, together with the high generality (23 examples) and robustness (up to gram scale) make this process a useful synthetic platform for the construction of structurally strained heterocycles. Abstract : From oxindole with flow: Oxindole enol ethers are engaged in microfluidic visible‐light Paternò–Büchi processes, allowing the concomitant C2‐C3 functionalisation of the biorelevant heterocyclic core, in high yield and selectivity.